REVITALISASI PASAR TRADISIONAL DI INDONESIA - Dewi Restu Mangeswuri; Niken Paraminta Purwanto (Jurnal Ekonomi & Kebijakan Publik, 2010)
In order to grow and develop traditional market, the market management should be comfortable to the counsuers’ traditional market satisfied. Trading in traditional market highly depends on their services in which a better facility should be made in order to increase customers. This study aims to distinguish between traditional and moderen market, with using the comparatble by strength and weakness of both market. The facts showed that the moderen market grown rapidly, while traditional market in stagnant. This mean, market traditional is likely without improved for long time. It needs a clear and strict regulation from government for empowering traditional market to grow and similar with moderen market in order to make harmony in mutual needs, mutual strengthening as well as mutual benefits.